Stretchable plasmonic metasurfaces for deformation monitoring - Li Peiyang; Gao Kaikai; Ma Ruize; Pan Kai; Li Dong; Liu Feng; Li Peng; Gan Xuetao; Zhao Jianlin; Wen Dandan (Nanophotonics)
Metasurfaces have recently gained significant attention due to the strong capacity in light field manipulation. However, most traditional metasurfaces are fabricated on rigid substrates, which fix their functionality after fabrication and limit their applications in dynamic measurement fields. In this work, we designed and fabricated a silver metasurface embedded in a stretchable substrate for sensing applications. This metasurface can generate different point cloud patterns under varying stretch ratios when illuminated by a laser beam. By collecting and analyzing the patterns, we can precisely reconstruct the deformation of the metasurface. Furthermore, the sample exhibits excellent performance under incident light of various wavelengths. These results pave the way for developing microdevices with novel capabilities based on flexible metamaterials.